The Effect of Tax Planning, Tax Avoidance and Profitability on Company Value With Financial Performance as Intervening Variables - Danang Puguh Wibowo; Sri Widyastuti; Murtanto Murtanto; Aris Riantori Faisal (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Tax is a mandatory contribution that is considered a burden by both the community and the company. Companies can minimize the burden that arises from these taxes by means of tax planning. One way of tax planning is to do tax avoidance. This method is expected to minimize the burden and optimize the value of the company. With optimal profit can increase the value of the company accompanied by good financial performance as well. The purpose of this study was to determine the effect of Tax Planning, Tax Avoidance and Profitability on Company Value with Financial Performance as Intervening Variable. This study uses secondary data obtained from the Indonesia Stock Exchange, amounting to 54 companies. The sample in this study were 30 companies in the consumer goods industry sector using purposive sampling method. The data used in this study is secondary data in the form of financial statements listed on the IDX for the 2016 - 2020 period. With panel data regression analysis, F test, t test, and Coefficient of Determination Test processed using Eviews 12.